Uzņēmējdarbības vides analīze Latvijā - Narbute, Inga (Latvijas Universitāte, 2007)
Izvēlēta bakalaura darba tēma ir “Uzņēmējdarbības vides analīze Latvijā”. Izveidot konkurētspējīgu ekonomiku nav iespējams bez uzņēmējdarbībai labvēlīgas vides radīšanas. Latvijā tiek konsekventi uzlabota uzņēmējdarbības vide un ir panākts ievērojams progress un uzlabojumi uzņēmējdarbības reģistrēšanā, nodokļu politikā, muitas likumdošanā, robežšķērsošanas procedūrās, būvniecībā u.c. jomās, tomēr vēl joprojām ir virkne neatrisinātu jautājumu un problēmu, kas ierobežo uzņēmējdarbību. Bakalaura darba mērķis ir izpētīt uzņēmējdarbības makro vidi un uzņēmējdarbības attīstību raksturojošos rādītājus Latvijā, kā arī atklāt labvēlīgas uzņēmējdarbības vides izveidi kavējošos faktorus un izstrādāt priekšlikumus to novēršanai. Bakalaura darbam ir gan teorētiska, gan praktiska nozīme. Tas ir izmantojams gan kā mācību, gan kā informatīvs materiāls par Latvijas uzņēmējdarbības vidi, problēmām, kas ierobežo uzņēmējdarbību un uzņēmējdarbības attīstības iespējām Latvijā. Atslēgas vārdi: uzņēmējdarbības vide, konkurētspēja, Komerclikums, uzņēmējdarbības formas.

The theme of bachelor work is “The analysis of business environment in Latvia”. To create a competition-capable economy it is not possible without creating well-disposed environment for it. In Latvia the environment for business is consistently improving and considerable progress and improvements have been made in legal registration, in the policy of taxes, in the legislation of duty, in border crossing procedures, in construction department and other areas, however still there are couple unsolved questions and problems, which limit business activities. The purpose of work is to explore business macro environment and find the characterizing pointers for development in business activities in Latvia, and also detect formation of well-disposed environment factors, setback factors and to deliver suggestions for their prevention. Bachelor work has both theoretical and practical value. It can be used both as learning and as informative material about the environment of business activities in Latvia, problems and business development potential in Latvia. Key words: environment of business activities, competitivity, Commerce law, forms of business.
Business environment analysis in Latvia
Keywords: Ekonomika